Scientific opinion on the relationship between intake of alpha‐lipoic acid (thioctic acid) and the risk of insulin autoimmune syndrome. (3rd June 2021) - ,; Turck, Dominique; Castenmiller, Jacqueline; de Henauw, Stefaan; Hirsch‐Ernst, Karen Ildico; Kearney, John; Knutsen, Helle Katrine; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Pelaez, Carmen; Pentieva, Kristina; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on the relationship between alpha‐lipoic acid (ALA) and the risk of insulin autoimmune syndrome (IAS). The Panel was also asked to advise on the dose below which ALA added to foods is not expected to cause IAS. A review of all possible adverse effects associated with consumption of ALA was not requested. This mandate refers to the procedure under Article 8(2) of Regulation (EC) No 1925/2006 on addition of vitamins, minerals and certain other substances to foods. No pre‐established rule exists for the evaluation of the safety of foods when classical toxicity tests cannot be used, e.g. for autoimmune diseases. Published scientific evidence was retrieved through comprehensive literature searches, particularly 49 case reports in which IAS developed following ALA consumption. In all cases, IAS resolved after a few weeks to months when ALA was discontinued. No publication linking the intake of ALA naturally occurring in foods to IAS was identified. The Panel concludes that the consumption of ALA added to foods, including food supplements, is likely to increase the risk of developing IAS in individuals with certain genetic polymorphisms, who cannot be readily identified without genetic testing. The plausible mechanism of such an effect has not yet been fully elucidated. The incidence of IAS in Europe is low and likely lower than in Japan where it has been estimated to be 0.017 per 100, 000 inhabitants in 2017–2018. Considering the limited data available, the risk associated with the development of IAS following ALA consumption cannot be quantified precisely. An ALA dose below which IAS is not expected to occur is likely to vary between individuals and cannot be determined from the available data.